Semen Analysis of Covid-19 Survivors and Uninfected Men: Examining the Motility, Concentration, Vitality, and Morphology Parameters of Spermatozoa - Musta'ina, Sri; Siswidiyanto, Eko Budi; Narulita, Pety; Agustinus,; Hinting, Aucky; Atika,; Faizah, Zakiyatul (Folia Medica Indonesiana, 2024)
Highlights: 1. Spermatozoa can be affected by coronavirus disease 2019 (COVID-19) due to a disruption in spermatogenesis, leading to a decline in semen quality. 2. This study compared the semen quality of COVID-19 survivors and those who had not been infected with COVID-19, specifically on the first spermatogenesis cycle following the confirmation of COVID-19 infection. 3. This study is distinctive since no previous research in Indonesia has examined the semen quality parameters, such as the concentration, morphology, motility, and vitality of spermatozoa, in men who had a COVID-19 infection. Abstract Semen quality in COVID-19 patients shows inconsistencies and variations. This research was conducted considering that health is the main capital for humans in Indonesia's development, as outlined in Sustainable Development Goal 3. The purpose of this study was to compare the semen quality of COVID-19 survivors with non-COVID-19 men. This study was an analytical observational study with a cross-sectional design. Subjects were selected through consecutive sampling of up to 26 men of childbearing age who met the predetermined criteria. Semen quality assessment using the WHO Semen Analysis Guide 6th edition. Quantitative data were analyzed using SPSS. The data normality test was carried out using the Saphiro-Wilk test. Then, the data were tested by t-test from two unpaired samples and by the Mann-Whitney test. Data from semen analysis based on COVID-19 severity were tested using variant analysis (One-way ANOVA) and the Kruskal Wallis test. The normal morphology of spermatozoa in COVID-19 survivors was significantly lower (p=0.011) compared to uninfected men. Other semen quality parameters did not differ significantly, although they were lower in COVID-19 survivors. The results of the analysis also showed no significant difference in semen parameters related to COVID-19 severity (p=0.488 for progressive motility; p=0.372 for non-progressive motility; p=0.325 for total motility; p=0.707 for immotility; p=0.412 for vitality; p=0.324 for concentration; and p=0.334 for normal morphology). The study provides evidence that COVID-19 survivors have a lower normal spermatozoa morphology compared to uninfected men. However, the motility, vitality, and concentration of spermatozoa did not differ significantly between the two groups.